Bionic composite metamaterials for harvesting of microwave and integration of multifunctionality. (1st March 2021) - Huang, Lingxi; Duan, Yuping; Liu, Jia; Zeng, Yuansong; Ma, Guojia; Pang, Huifang; Zhang, Weiping
Abstract: Perfect stealth has attracted humanity for decades owing to the advent of metamaterials, however, despite long-standing efforts in design and fabrication, it has been challenging to achieve ultra-broadband absorption under deep-subwavelength thickness, the fundamental hurdle is Plank-Rozanov limit, which hindering the development of stealth materials. Herein, inspired by the absorption model of Pachliopta aristolochiae, present works demonstrate an approach with composition concept to ideal stealth, through the synergy of microwave melanin and bionic metastructure, the fabricated biomimetic metamaterials exhibit effective absorption over 2–18 GHz range under 0.04 λmax thickness for radar stealth, which breakthrough the Plank-Rozanov limit by utilizing the enhanced resonance of bionic metastructure in absorption, corresponding mechanisms are demonstrated by simulation models. The metamaterials also robustness for arrangement and polarizations, compatible infrared emissivity is reduced to 0.43, as well as flexibility and impact resistance during minus temperature. The principle behind here is universal and can be extended to many metamaterials and a broad range of absorption. Graphical abstract: Image 1